Activity of rat Mx proteins against a rhabdovirus. - Meier, E (1990)
Upon stimulation with alpha/beta interferon, rat cells synthesize three Mx proteins. Sequence analysis of corresponding cDNAs reveals that these three proteins are derived from three distinct genes. One of the rat cDNAs is termed Mx1 because it is most closely related to the mouse Mx1 cDNA and because it codes for a nuclear protein that, like the mouse Mx1 protein, inhibits influenza virus growth. However, this protein differs from mouse Mx1 protein, in that it also inhibits vesicular stomatitis virus (VSV), a rhabdovirus. A second rat cDNA is more closely related to the mouse Mx2 cDNA and directs the synthesis of a cytoplasmic protein that inhibits VSV but not influenza virus. The third rat cDNA codes for a cytoplasmic protein that differs from the second one in only eight positions and has no detectable activity against either virus. These results indicate that rat Mx proteins have antiviral specificities not anticipated from the analysis of the murine Mx1 protein.